2009
DOI: 10.1007/s00221-009-2088-7
|View full text |Cite
|
Sign up to set email alerts
|

Armed against falls: the contribution of arm movements to balance recovery after tripping

Abstract: Arm movements after perturbations like tripping over an obstacle have been suggested to be aspecific startle responses, serve a protective function or contribute to balance recovery. This study aimed at determining if and how arm movements play a functional role in balance recovery after a perturbation. We tripped young subjects using an obstacle that suddenly appeared from the floor at exactly mid-swing. We measured arm muscle EMG, quantified body rotations after tripping, and established the effects of arm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 31 publications
7
132
4
1
Order By: Relevance
“…The ipsilateral arm works to reduce the moment of inertia in the coronal plane, which provides stability in the coronal plane. Muscle activities inducing these arm motions can be observed within 100 msec after trips [PWRvD08].…”
Section: Arm Motions During Responses To Tripsmentioning
confidence: 98%
See 1 more Smart Citation
“…The ipsilateral arm works to reduce the moment of inertia in the coronal plane, which provides stability in the coronal plane. Muscle activities inducing these arm motions can be observed within 100 msec after trips [PWRvD08].…”
Section: Arm Motions During Responses To Tripsmentioning
confidence: 98%
“…Therefore, we picked one motion trajectory in which the subject used the same strategy as in the current simulated motion, and used that trajectory as the target arm joint angles. We use the timing of shoulder responses reported by Pijnappels and colleagues [PWRvD08] and the offset between muscle activity and torque generation to activate the shoulders and elbows. After the front leg touches down and the state becomes Single Support After Trip, the arms are activated to perform swings similar to normal walking.…”
Section: Simulation Of Upper Body Motionmentioning
confidence: 99%
“…However, Hu et al [7] found even greater effects of excessive arm swing on stability in an elderly cohort, suggesting that effects that could be obtained in elderly would be under estimated rather than over estimated. Future studies should explore possible effects of excessive arm swing instruction on regaining stability after a perturbation [5,6]. Subjects were mostly well able to perform the different coordination patterns; with only some slightly worse performances during a limited number of strides.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Historically, studies of balance-recovery reactions have tended to focus primarily on the lower limbs; however, there is an increasing awareness that rapid movements of the upper limbs also play an important role in stabilizing the body, both in daily life McIlroy 1996, 1997;Rabinovitch et al 2009) and in experimental settings (Romick-Allen and Schultz 1988;McIlroy and Maki 1995b;Maki and McIlroy 1997;Tang et al 1998;Allum et al 2002;Marigold and Patla 2002;Marigold et al 2003;Misiaszek 2003;Cham and Sandrian 2007;Roos et al 2008;Pijnappels et al 2010). In the event that attempts to recover balance are unsuccessful, arm reactions may also act to help absorb the energy of the fall and protect against head injury (Roberts 1978) or hip fracture (Feldman and Robinovitch 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Even small balance perturbations can evoke arm reactions, particularly when the perturbation is novel or unexpected (Maki and Whitelaw 1993;Corbeil et al 2004), and it has been proposed that the arm movements can help to stabilize the body through various 'counter-balancing' inertial or gravitational mechanisms (Romick-Allen and Schultz 1988; Allum et al 2002;Marigold and Patla 2002;Marigold et al 2003;Misiaszek 2003;Hoff 2007;Marigold and Misiaszek 2009;Roos et al 2008;Pijnappels et al 2010).…”
Section: Introductionmentioning
confidence: 99%